2018
DOI: 10.1177/1071100718764674
|View full text |Cite
|
Sign up to set email alerts
|

Tendoscopic Treatment of Peroneal Intrasheath Subluxation: A New Subgroup With Superior Peroneal Retinaculum Injury

Abstract: Level IV, case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0
13

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 48 publications
1
28
0
13
Order By: Relevance
“…The fibular groove may be deepened directly using a chisel, mallet, motorized shaver, or burr. 1 , 7 , 28 , 29 The Zoellner and Clancy technique entails formation of an osteoperiosteal flap along the posterolateral distal fibula and lateral malleolus, whose medial side remains attached to the fibula and acts as a hinge. The flap is swung posteriorly along this hinge and fixated, directly deepening the groove.…”
Section: Discussionmentioning
confidence: 99%
“…The fibular groove may be deepened directly using a chisel, mallet, motorized shaver, or burr. 1 , 7 , 28 , 29 The Zoellner and Clancy technique entails formation of an osteoperiosteal flap along the posterolateral distal fibula and lateral malleolus, whose medial side remains attached to the fibula and acts as a hinge. The flap is swung posteriorly along this hinge and fixated, directly deepening the groove.…”
Section: Discussionmentioning
confidence: 99%
“…SPR connections are essential components of a functional complex at the lateral malleolus level (12,27) . Statistically significant differences in the occurrence of connections revealed on MRI between the ATFL and PTS were noticed before between groups of single and double fascicular ATFL and CFL (11) .…”
Section: Discussionmentioning
confidence: 99%
“…This condition is characterized by retrofibular pain and painful clicking of the tendons without disruption of the superior peroneal retinaculum. 13,18,28,34,43 Raikin et al 34 showed 14 cases with PL tendon subluxation around or through the PB tendon without interruption of the superior peroneal retinaculum. The open groove-deepening procedure has successfully managed all cases.…”
Section: Discussionmentioning
confidence: 99%
“…All of them showed signs of tenosynovitis while 2 had a new peroneal tendon tear, 3 had noted LLMB, and 2 had PQ muscle present. 46 Analysis by Guelfi et al 18 of 12 patients with intrasheath subluxations showed that 4 patients had partial PB tendon tear, 4 had LLMB, and 3 had PQ muscle present. We observed LLMB in 7 of 8 cases with intrasheath subluxation of the peroneal tendons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation